Trust among millennial generation domestic travelers in staying at eco-friendly hotels - Mayang Fitri Anggani; I Gusti Agung Febrianto (Jurnal Pariwisata Pesona, 2024)
This research aims to determine the beliefs of millennial domestic tourists regarding their intention to stay at an environmentally friendly hotel. The millennial generation is known as a group that has high sensitivity to social and environmental issues. Tourists' belief in environmentally friendly hotels is the belief that the hotel consistently implements policies and actions oriented towards environmental preservation, such as efficient resource management and reducing negative impacts on the environment. Consumer belief includes their perception of a hotel's commitment to implementing real sustainable practices and not just green marketing efforts. Intention to stay at an eco-friendly hotel is influenced not only by individual preferences, but also by the extent to which tourists believe that the hotel can meet their expectations. This research focuses on domestic tourists from the millennial generation, consisting of 100 respondents. Next, the data was analyzed using quantitative descriptive methods. The results of this research show that millennial generation domestic tourists believe that environmentally friendly hotels have high value and quality and have sustainable benefits. The intention of domestic tourists from the millennial generation is also very high. This means that high intention shows a sense of concern for environmentally friendly hotels that support sustainability and benefit the environment.